The Itinerant 2D Electron Gas of the Indium Oxide (111) Surface: Implications for Carbon‐ and Energy‐Conversion Applications. Issue 12 (5th September 2019) - Jovic, Vedran; Moser, Simon; Papadogianni, Alexandra; Koch, Roland J.; Rossi, Antonio; Jozwiak, Chris; Bostwick, Aaron; Rotenberg, Eli; Kennedy, John V.; Bierwagen, Oliver; Smith, Kevin E.
Abstract: Transparent conducting oxides (TCO) have integral and emerging roles in photovoltaic, thermoelectric energy conversion, and more recently, photocatalytic systems. The functional properties of TCOs, and thus their role in these applications, are often mediated by the bulk electronic band structure but are also strongly influenced by the electronic structure of the native surface 2D electron gas (2DEG), particularly under operating conditions. This study investigates the 2DEG, and its response to changes in chemistry, at the (111) surface of the model TCO In2 O3, through angle resolved and core level X‐ray photoemission spectroscopy. It is found that the itinerant charge carriers of the 2DEG reside in two quantum well subbands penetrating up to 65 Å below the surface. The charge carrier concentration of this 2DEG, and thus the high surface n‐type conductivity, emerges from donor‐type oxygen vacancies of surface character and proves to be remarkably robust against surface absorbents and contamination. The optical transparency, however, may rely on the presence of ubiquitous surface adsorbed oxygen groups and hydrogen defect states that passivate localized oxygen vacancy states in the bandgap of In2 O3 . Abstract : In2 O3 is an archetype transparent conducting oxide with established and emerging roles in optoelectronic and energy conversion applications. At the (111) surface, its optical transparency relies on ubiquitous donor type hydrogen defects, while the electrical conductivity associated with the itinerant 2D electron gas is mediated by the oxygen defect of strictly surface character.